PEMBERDAYAAN MASYARAKAT DALAM UPAYA PENCEGAHAN STROKE DI KELURAHAN TARATARA SATU - Langingi, Ake (Journal of Excellence Humanities and Religiosity, 2024)
About a third of stroke sufferers in the world experience permanent disability. Stroke occurs when the brain's blood vessels fail to supply oxygen to the brain cells or when the brain cells do not receive nutrients and oxygen from the blood. Stroke symptoms usually appear suddenly, with loss of strength on one side of the body, confusion, difficulty speaking and understanding, problems with vision, difficulty walking, headaches, and loss of balance. This can be prevented from happening by adopting a healthy lifestyle. The service method used is the lecture and question and answer method with people who are at risk of stroke. The result of this service activity is that there has been an increase in public knowledge about stroke prevention, which is the result of this service activity. This activity is also very important to carry out, especially targeting people with hypertension who are no longer able to comply with taking anti-hypertension medication and adopting a healthy lifestyle, so they need to provide education or socialization about stroke prevention.